Forecasting index of unfavorable outcomes of systemic lupus erythematosus - E. A. Aseeva; N. Yu. Nikishina; A. A. Mesnyankina; S. K. Solovyev; B. Sh. Isaeva; G. M. Koilubaeva; A. M. Lila (Современная ревматология)
The development of irreversible organ damage (IOD) in systemic lupus erythematosus (SLE) significantly increases the risk of death, worsens the quality of life and significantly increases the cost of treatment. The development and implementation of specific tools that will promote early identification of the risk of unfavorable outcomes is a priority. The article presents literature review on a new method for prediction of unfavorable outcomes in SLE – frailty index (FI, vulnerability index). FI, developed by a group of international experts on the basis of the database of the international cohort of SLE patients – SLICC (Systemic Lupus International Collaborating Clinics) – is easily reproducible in real clinical practice and can be used in patients with an early stage of SLE to predict the risk of death, the development of IOD. and hospitalization. The SLE Forecasting index of unfavorable outcomes (SLICC-FI) appears to be a promising clinical and research tool for identifying those who need more careful monitoring and an individual therapeutic strategy at an early stage of the disease.